Vận dụng mô hình CIPO trong quản lí đào tạo nhân lực du lịch tại các trường đại học - một số vấn đề lí luận - Lê, Thị Thanh Hoa (Tạp chí Giáo dục, 2024)
For the tourism industry, human resources are considered a valuable asset, directly impacting the business performance of businesses as well as the development of the tourism industry. Improving the quality of tourism human resource training at universities to meet social needs is an extremely urgent and necessary issue in the current period. The current context of international integration poses high requirements and opportunities and challenges for training high-quality tourism human resources. Appropriate measures are needed to improve the quality of tourism human resource training at universities. The article proposes to apply the CIPO model to manage tourism human resource training at universities through managing training input elements; managing the training process; managing training output elements; managing the impact of context on tourism human resource training management. Applying the CIPO model to managing tourism human resource training at universities will improve the quality of tourism human resource training at universities in the current period.